Does blood flow restriction influence the maximal number of repetitions performed during the bench press - Rawska, M.; Gepfert, M.; Mostowik, A.; Krzysztofik, M.; Wojdala, G.; Lulinska, A.; Wilk, M. (Baltic Journal of Health and Physical Activity, 2019)
The main goal of the presented study was to assess the effect of blood flow restriction (BFR) on the maximum number of repetitions in the bench press exercise (BP) with different movement tempos. Material and methods: Four female athletes volunteered for the study. The experiment was performed following a randomized crossover design, with four different testing protocols: 2/0/X/0 fast tempo with BFR (FASTBFR); 2/0/X/0 fast tempo without BFR (FASTNO-BFR); 6/0/X/0 slow tempo with BFR (SLOWBFR) or 6/0/X/0 slow tempo without BFR (SLOWNO-BFR). During the experimental session, participants performed 5 sets of the BP at 80%1RM. The following variables were recorded: the maximal number of repetitions in every set (REPSet1-5) and the total number of repetitions performed in 5 sets (TREP). One-way ANOVA was used to show differences between variables. Results: There were significant differences between FASTNO-BFR and SLOWNO-BFR, between FASTBFR and SLOWBFR variables in REPSet1-5 (p < 0.05) and TREP (p < 0.01). Similarly, there were significant differences between FASTNO-BFR and FASTBFR variables in REPSet1,2,5 (p < 0.05) and TREP. Significant differences between SLOWNOBFR and SLOWBFR variables were also found in REPSet1,5 (p < 0.05), as well as in TREP (p < 0.01) Conclusions: The use of BFR in resistance training improves the maximal number of REP during the BP.